$(\min, \max)$-equivalence of posets and nonnegative Tits forms - Bondarenko, V. M.; Stepochkina, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study the relationship between the (min, max)-equivalence of posets and properties of their quadratic Tits form related to nonnegative definiteness. In particular, we prove that the Tits form of a poset S is nonnegative definite if and only if the Tits form of any poset $(\min, \max)$-equivalent to S is weakly nonnegative.